Atom‐probe analyses of nanodiamonds from Allende. (4th March 2014) - Heck, Philipp R.; Stadermann, Frank J.; Isheim, Dieter; Auciello, Orlando; Daulton, Tyrone L.; Davis, Andrew M.; Elam, Jeffrey W.; Floss, Christine; Hiller, Jon; Larson, David J.; Lewis, Josiah B.; Mane, Anil; et al.
Abstract Atom‐probe tomography (APT) is currently the only analytical technique that, due to its spatial resolution and detection efficiency, has the potential to measure the carbon isotope ratios of individual nanodiamonds. We describe three different sample preparation protocols that we developed for the APT analysis of meteoritic nanodiamonds at sub‐nm resolution and present carbon isotope peak ratios of meteoritic and synthetic nanodiamonds. The results demonstrate an instrumental bias associated with APT that needs to be quantified and corrected to obtain accurate isotope ratios. After this correction is applied, this technique should allow determination of the distribution of 12C/13C ratios in individual diamond grains, solving the decades‐old question of the origin of meteoritic nanodiamonds: what fraction, if any, formed in the solar system and in presolar environments? Furthermore, APT could help us identify the stellar sources of any presolar nanodiamonds that are detected.